Respuesta :

Answer:

For this equation the value of x is - 2/3

Step-by-step explanation:

1. Resolving the equation 2/3-4x+7/2=-9x+5/6

-4x + 9x = 5/6 - 2/3 - 7/2 (Putting the all the x values on the left)

5x = (5/6 - 4/6 -21/6)

5x = -20/6

x = - 20/6 /5 (Dividing by 5 at both sides)

x = -20/6 * 1/5

x = -4/6 = - 2/3 (Simplifying)

2. Proof of replacing x by -2/3

2/3 - 4 (-2/3) + 7/2 = -9 (-2/3) + 5/6

2/3 + 8/3 + 7/2 = 18/3 + 5/6

10/3 + 7/2 = 6 + 5/6

20 + 21 = 36 + 5 (Multiplying by 6 at both sides)

41 = 41

It means the value of -2/3 for x is correct

Note: Same answer than 13866851

Answer:

this is both the answers in case anyone wanted them

Step-by-step explanation:

Step-by-step explanation:

Ver imagen ym039961